Analiza podizanja vjetrozaštitnih pojasa na mediteranskom kršu Hrvatske Analysis of raising windbreaks on the mediterranean karst of Croatia - Barčić, Damir; Habjanec, Vlado; Španjol, Željko; Šango, Mario (2021)
Vjetrozaštitni pojasi uspostavljaju se kao barijere od redova stabala ili grmlja koje se sade s namjenom reduciranja brzine vjetra, smanjenja evapotranspiracije, zaštite od eolske erozije, istovremeno izravno se koriste za zaštitu kultura i nasada te osiguravaju povoljnije stanišne uvjete. Jedna od bitnih pretpostavki uspjeha podizanja pojasa je korištenje autohtonih vrsta drveća i grmlja prilagođenih na stanišne uvjete. Tehnologije i postupci zaštite mogu biti usmjerene na biološko-tehničke postupke pošumljivanja i podizanja nasada s ciljem ublažavanja udara vjetra. Izbor biljnih vrsta za podizanje nasada uvjetovan je različitim klimatskim zonama, biološko-ekološkim značajkama vrsta, ali i kompoziciji s ostalim elementima krajobraza. Zaštita od vjetra postavlja se prema pravcu udara glavnog vjetra. Uspostava vjetrozaštitnih pojasa ponajprije smanjuje snagu vjetra i reducira njegovu brzinu. Na taj način ublažavaju se klimatski ekstremi povezani s olujnim vjetrom (na kršu se ponajprije radi o buri) i utječe na mikroklimatske uvjete, što u konačnici može osigurati zaštitu poljoprivrednog i šumskog zemljišta.
Windbreaks are established as barriers of rows of trees or shrubs that are planted to reduce wind speed, reduce evapotranspiration, protect against aeolian erosion, while being used directly to protect crops and plantations and provide favorable habitat conditions. One of the essential preconditions for the success of belt raising is the use of indigenous species that are adapted to habitat conditions. Technologies and protection procedures can be focused on biological-technical procedures of afforestation and raising plantations with the aim of mitigating wind gusts. The goal of windbreaks and raising plantations with different species is shown in the following figures (Figures 3,4,5,6,7). The choice of plant species for raising plantations is conditioned by different climatic zones, biological and ecological characteristics of the species, but also the composition with other elements of the landscape. An important feature of windbreaks is their wind permeability and impact on wind speed. Permeability depends on the habitus of the plant, and the type of trees and shrubs. The density of the windbreak changes its impact and effectiveness; the permeable belt ensures a balanced distribution as part of the wind skips it and part passes through the belt. The wind protection is placed in the direction of the main wind. Technical wind protection procedures include the construction of barriers made of building materials such as brick, stone, timber, glass, hard plastic or a combination of several types of materials (Figures 1 and 2). Biological procedures in terms of species selection and consideration of habitat conditions are much more complex. All this in the context of frequent changes in the “wind structure” in the karst area. Belt lifting can be differentiated according to purpose and expected performance as follows: impermeable belt, semi-permeable and permeable belt. The establishment of windbreaks primarily reduces wind strength and reduces its speed.
Bibliografija: str 182-183.
Sažetak ; Summary.
Keywords: Vjetar -- Propusnost -- Vjetrozaštita -- Mikroklima -- Erozija -- Zaštita tla; Hrvatska